Adverse Childhood Experiences Are Linked to Age of Onset and Reading Recognition in Multiple Sclerosis - Shaw, Michael T.; Pawlak, Natalie O.; Frontario, Ariana; Sherman, Kathleen; Krupp, Lauren B.; Charvet, Leigh E. (Frontiers in Neurology, 2017)
Abstract Background: Adverse childhood experiences exert a psychological and physiological toll that increases risk of chronic conditions, poorer social functioning, and cognitive impairment in adulthood. Objective: To investigate the relationship between childhood adversity and clinical disease features in multiple sclerosis (MS). Methods: Sixty-seven participants with MS completed the Adverse Childhood Experiences (ACE) assessment and neuropsychological assessments as part of a larger clinical trial of cognitive remediation. Results: ACE scores, a measure of exposure to adverse events in childhood, significantly predicted age of MS onset (r= 0.30, p=0.04). ACE’s were also linked to reading recognition (a proxy for premorbid IQ); (r= 0.25, p=0.04). ACE scores were not related to age, current disability, or current level of cognitive impairment measured by the Symbol Digit Modalities Test (SDMT). Conclusion: Childhood adversity may increase the likelihood of earlier age of onset and poorer estimated premorbid IQ in MS.